New guidelines, and a new hypertensive population How to select women for menopausal hormone therapy - Pacheco-Romero, José (2018)
The 2017 ACC/AHA/AAPA/ABC/ACPM/ AGS/APhA/ASH/ASPC/NMA/PCNA Guideline for the Prevention, Detection, Evaluation, and Management of High Blood Pressure in Adults published in November 2017(1) designates new categories of blood pressure in adults: Normal <120/140/>90 mm Hg. A previous report based on blood pressure readings in 19.1 million adults pooled from 1 479 studies found that the global age-standardized prevalence of raised blood pressure was 24.1% (21.4–27.1) in men and 20.1% (17.8–22.5) in women in 2015(2). The Peruvian Tornasol II study on Risk Factors for Cardiovascular Diseases reported in 2011 a prevalence of 27.3% for arterial hypertension(3), showing an increase compared to the previous value of 23.7% in 2006(4).